Pengaruh Konsentrasi Palm Oil Mill Effluent (POME) Kinerja Konsorsium Mikroalga-Bakteri Dari Palm Oil Mill Effluent (POME) Untuk Produksi Lipid Menggunakan Multitubular Airliftbioreactor - Andhika Chandra; Shinta Elystia; Sri Rezeki Muria (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Palm Oil Mill Effluent (POME) is wastewater that has high organic mattercontent. The treatment process of Palm Oil Mill Effluent (POME) generally with the open pond system can be one of the contributors of greenhouse gases in the form of CO2 and CH4 gases. To prevent the release of greenhouse gases, microalgae are used by using POME which contains organic ingredients as a nutrition source for microalgae cultivation media to produce raw materials for biofuel (in the form of lipids and carbohydrates) that can be used to overcome the energy crisis. In this study, a microalgae-bacteria consortium of POME wascultivated in POME medium with a variation of injection of CO2 gas flow with variations (0,3; 0,5; 0,7) l/minute. The cultivation process was carried out for 13 days with radiation using sunlight. The results showed that at a flow rate of 0.5 l /min the lipid content was 45.21% of dry weight with μ = 0.850 / day. Theefficiency of removal of organic matter in the form of COD and total nitrogen is 87,36% and 69.92%.Keywords: Consortium, Microalgae, Indigenous, CO2 , Flow rate, Injection , Lipid, COD, Nitrogen total, Palm Oil Mill Effluent (POME)